Outpatient-based physical rehabilitation for survivors of prolonged critical illness: A randomized controlled trial. (2nd April 2016) - McWilliams, David J.; Benington, Steve; Atkinson, Dougal
ABSTRACT: Introduction : The physical and psychological impact of critical illness is well documented. Recovery may take many months and is often incomplete. The optimal way of addressing these important sequelae following hospital discharge remains unclear. Methods : Single center, randomized controlled trial in patients invasively ventilated for ≥5 days. The treatment group (TG) underwent a 7-week, outpatient-based exercise and education program, with the control group (CG) receiving no intervention during the study period. Primary outcome measures were changes in functional capacity assessed using the cardiopulmonary exercise testing parameters, peak VO2, and anaerobic threshold (AT). Secondary outcome measures were changes in and health-related quality of life assessed using the Short Form 36 version 2 questionnaire. Assessors remained blinded to group allocation. Results : Sixty-three patients completed the study (target n = 90). Improvements in both peak VO2 and AT were seen in both TG and CG but no significant difference between groups was evident. AT improved by 11.7% in CG (baseline 10.3 ml O2 kg −1 min −1, follow-up 11.5 ml O2 kg −1 min −1 ), and by 14.6% in TG (baseline 10.3 ml O2 kg −1 min −1, follow-up 11.8 ml O2 kg −1 min −1 ; ANCOVA p = 0.74). Peak VO2 improved by 14.0% in CG (baseline 13.6 ml O2 kg −1 min −1, follow-up 15.5 ml O2 kg −1 min −1 ), and by 18.8% in TG (baseline 13.8 ml O2 kg −1 min −1, follow-up 16.4 ml O2 kg −1 min −1 ; ANCOVA p = 0.68). Significant improvements were seen in both groups for physical component summary scores (PCS) (TG 39.6 versus 31.0; CG 36.1 versus 32.6) and mental component summary scores (MCS) (TG 48.6 versus 38.4; CG 41.3 versus 37.0). The degree of improvement was significantly higher in the treatment group in comparison to control subjects (PCS p = 0.048; MCS p = 0.017). This improvement was most marked in the subgroup ventilated for >14 days. Conclusions : A 7-week, outpatient-based exercise and education program resulted in improved health-related quality of life scores but not improved exercise capacity.